2014
DOI: 10.1007/s10608-014-9639-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Standards on State Anxiety, Appraisal Processes, and Negative Pre- and Post-event Rumination in Social Anxiety Disorder

Abstract: Cognitive models emphasise the importance of pre-and post-event rumination as maintaining factors of Social Anxiety Disorder (SAD), however, there is limited research investigating pre-event rumination. This study aims to examine several key hypotheses posited by the cognitive models by experimentally manipulating social standards in order to examine the impact of high and low perceived social standards on appraisal processes, state anxiety, and negative rumination, and to determine if the predictors of pre-ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
0
23
1
2
Order By: Relevance
“…Anticipatory rumination (AR) has only recently become a focus of empirical attention; however, a limited body of research supports cognitive models of AR in social anxiety and suggest that it is a maintaining factor specific to social anxiety (Mills, Grant, Lechner, & Judah, 2014). Correlational studies indicate that high socially anxious individuals engage in more AR prior to social or performance situations compared to low socially anxious individuals (Hinrichsen & Clark, 2003;Penney & Abbott, 2015;Vassilopoulos, 2004Vassilopoulos, , 2008, and that ruminative thoughts about upcoming social events tend to be recurrent and intrusive, increase anxiety, and interfere with concentration (Vassilopoulos, 2004). Furthermore, consistent with models of AR, highly socially anxious individuals report that they are more likely to dwell on ways of avoiding/escaping social situations, catastrophise about what might happen in the situation, engage in anticipatory safety behaviours, generate negative self-images from an observer perspective, and produce fewer positive autobiographical memories and more negative-evaluative thoughts compared to low socially anxious individuals (Chiupka, Mosovitch, & Bielak, 2012;Hinrichsen & Clark, 2003;Vassilopoulos, 2008).…”
Section: Anticipatory Rumination In Social Anxietymentioning
confidence: 99%
“…Anticipatory rumination (AR) has only recently become a focus of empirical attention; however, a limited body of research supports cognitive models of AR in social anxiety and suggest that it is a maintaining factor specific to social anxiety (Mills, Grant, Lechner, & Judah, 2014). Correlational studies indicate that high socially anxious individuals engage in more AR prior to social or performance situations compared to low socially anxious individuals (Hinrichsen & Clark, 2003;Penney & Abbott, 2015;Vassilopoulos, 2004Vassilopoulos, , 2008, and that ruminative thoughts about upcoming social events tend to be recurrent and intrusive, increase anxiety, and interfere with concentration (Vassilopoulos, 2004). Furthermore, consistent with models of AR, highly socially anxious individuals report that they are more likely to dwell on ways of avoiding/escaping social situations, catastrophise about what might happen in the situation, engage in anticipatory safety behaviours, generate negative self-images from an observer perspective, and produce fewer positive autobiographical memories and more negative-evaluative thoughts compared to low socially anxious individuals (Chiupka, Mosovitch, & Bielak, 2012;Hinrichsen & Clark, 2003;Vassilopoulos, 2008).…”
Section: Anticipatory Rumination In Social Anxietymentioning
confidence: 99%
“…El tamaño de la muestra va en línea de estudios similares que analizan el modo en que determinados factores influyen en la percepción de una noticia o de un asunto particular (ver por ejemplo: Da Silva & Pereira, 2017;Gerber et al, 2017;Penney & Abbott, 2015).…”
Section: Metodologíaunclassified
“…One such study by Rapee and Abbott (2007) found that trait social anxiety was related to negative post-event rumination via the cognitive processes of performance and threat appraisals. Furthermore, a study by Penney and Abbott (2014b) reported that of their theorised predictors of negative rumination (i.e., self-appraisal of performance, threat appraisals, self-efficacy, and state anxiety) only threat appraisals explained unique variance in post-event rumination following a speech task. This finding is surprising given the breadth of research supporting performance appraisals as a predictor of negative rumination and is yet to be replicated.…”
Section: Predictors Of Post-event Ruminationmentioning
confidence: 99%
“…However, a non-clinical student sample was used in this study, and immediately before completing a post-event rumination questionnaire participants were told they would have to complete another speech task, possibly inducing inflated post-event rumination frequency responses. The predictive relationship between self-efficacy and post-event rumination is also uncertain, with Penney and Abbott (2014b) reporting that self-efficacy does not explain unique variance in post-event rumination, but does so in pre-event rumination. Given this sparsity of research, the predictive utility of these cognitive processes for post-event rumination needs to be further researched.…”
Section: Predictors Of Post-event Ruminationmentioning
confidence: 99%